Policy Implementation in Transportation Office of Kediri City Regarding to Motor Vehicle Testing - Erlambang, Nanda; Haryono, Bambang Santoso; Hermawan, Romy (Jurnal Ilmiah Administrasi Publik, 2020)
This study aimed to describe policy implementation of motor vehicle testing and its suporting and inhibiting factors in Transportation Office of Kediri City. This study was descriptive research with qualitative approach by involving all of related parties of motor vehicle testing policy in Kediri City. Data collection techniques used were documentation, observation and interviews directly in actual field. Identification of problems using the theory of Edward III, 1980. Public policy implementation in Transportation Office of Kediri City was in accordance with the theory of policy implementation of Edward III, 1980 which included factors of communication, resources, disposition, and bureaucratic structure. The supporting factors for the policy implementation of motor vehicle testing in Kediri City through the Regional Technical Implementation Unit were the presence of accurate calibrated measurement tools and accreditation of institution with the predicate of B. The inhibiting factor was the absence of socialization activities in Kediri City regarding to the motor vehicle testing policies because there was no budget provided for the activities.